Risk Management and Safety Education in Custom Garage - N. Jamilatul Izyati; Irman Syahrul A.; Nadya Aulia A.; Rizki Amelia H.; Devina Aura I.; Alicia Rosalinda D. (Journal of Safety Education, 2023)
Workplace accidents and injuries are among the most important preventable health problems worldwide. In custom workshops, there are potential hazards that come from their work processes which consist of welding, painting, and finishing. Risk management systems are mostly not implemented in informal sectors such as car paint and welding workshops. The research was carried out to identify and analyze potential hazards in the Custom Garage. This research is a qualitative descriptive study. Data collection and processing techniques in this study were direct observation and interviews with leaders and owners of the Custom Garage. The research was conducted using the HIRAC (Hazard Identification, Risk Assessment, and Control) sheet instrument. Based on the results of hazard identification, there are 13 work process activities with 47 types of work risks with 15 risks that are included in the high category. The potential risk of accidents in the high category includes inhaling rust dust and residual welding fume, inhaling the smell of toxic substances such as rust, car paint, putty, thinner, and poxy, and there is a high potential for noise hazard.